Incidence of psychosocial conditioning factors of university drop-out in the carreer of bioengeniering of the UNSJ - Graffigna Vaggione, Juan Pablo (2020)
This work socializes the initial results corresponding to a doctoral thesis that includes a multiple approach, quali-quantitative, of the University Dropout in the Bioengineering Career of the UNSJ. It aims to know if the dropping-out, chronic and active students have significant differences in relation to certain psychosocial conditions. Here, in particular, some of these are addressed, namely: resilience, the number of hours they dedicate to work, the educational level achieved by the family of origin and the expectation / safety they had to complete the career at the beginning. For this, a sociodemographic survey (Aparicio, 2019) and the University Resilience Questionnaire (CREU, Peralta Díaz et al, 2006) were applied, which addresses 8 protective factors before adversity on 92 students and alumni. The sample was divided into three groups according to their academic condition and the correlation among the mentioned factors was evaluated. It turned out that the protective factor that most distinguishes defectors, chronic and active is the interaction. Likewise, it was evidenced that working more than 10 hours also proved to be discriminant regarding the possibility of permanence. Ultimately it is tried to distinguish among those factors on which the institution can intervene, from those external its possibility of incidence.